2017
DOI: 10.3390/genes8050145
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Telomere Maintenance for Therapeutic Interventions in Gliomas

Abstract: High-grade astrocytoma of WHO grade 4 termed glioblastoma multiforme (GBM) is a common human brain tumor with poor patient outcome. Astrocytoma demonstrates two known telomere maintenance mechanisms (TMMs) based on telomerase activity (TA) and on alternative lengthening of telomeres (ALT). ALT is associated with lower tumor grades and better outcome. In contrast to ALT, regulation of TA in tumors by direct mutation and epigenetic activation of the hTERT promoter is well established. Here, we summarize the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 172 publications
(241 reference statements)
1
16
0
Order By: Relevance
“…TERT regulation by miRNA was summarized by Lewis et al [ 420 ]. It was proposed that miRNAs can post-transcriptionally alter TERT transcripts directly or indirectly, affecting regulatory transcription factors [ 5 , 420 ]. TERRA transcripts are other types of non-coding RNAs found in eukaryotes that will be further addressed due to their association in ALT.…”
Section: Telomere Maintenance Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…TERT regulation by miRNA was summarized by Lewis et al [ 420 ]. It was proposed that miRNAs can post-transcriptionally alter TERT transcripts directly or indirectly, affecting regulatory transcription factors [ 5 , 420 ]. TERRA transcripts are other types of non-coding RNAs found in eukaryotes that will be further addressed due to their association in ALT.…”
Section: Telomere Maintenance Mechanismsmentioning
confidence: 99%
“…ATRX / DAXX mutations are thus suggested to be strong contributors to the activation of the ALT pathway. New evidence of epigenetic mechanisms affecting ALT were recently reported, such as microRNA regulation, as reviewed by Naderlinger et al [ 5 ]. This mechanism has also been reported to correlate with high levels of TERRA [ 456 ].…”
Section: Telomere Maintenance Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pieces of evidence have shown that the ALT mechanism is particularly responsive to telomeric epigenetic modifications [49]. Methionine restriction, which affects DNA methyltransferase (DNMT) activity, results in a rapid accumulation of APBs [50], whereas depletion of anti-silencing function 1a/1b histone chaperones, which coordinate the shuttling of histone proteins during DNA replication, or of histone deacetylase 5 (HDAC5), results in ALT induction (i.e., APB formation or telomere recombination) in telomerase-positive cancer cell lines [51,52].…”
Section: Preclinical Evidence Of Alt Activation As An Adaptive Responmentioning
confidence: 99%
“…Some reviews have already pointed out emerging targets for GBM therapy [ 128 , 129 , 130 , 131 ]. Here, we investigated the main studies focusing on Wnt pathways, which has been positively correlated to the genesis and progression of GBMs, as confirmed by the altered expression of different members of Wnt associated with a bad prognosis in GBM patients.…”
Section: Factors In the Wnt Pathway Considered Potential Targets Fmentioning
confidence: 99%